2000
DOI: 10.1021/la991233a
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle−Polymer Hybrid Architectures:  A Full Account of the Parachute Architecture

Abstract: We have previously reported that polymerization of styrene in dioctadecyldimethylammonium bromide (DODAB) vesicles leads to so-called parachute-like morphologies where a polymer bead is attached to a vesicle. To learn the constructive principles of these novel polymer colloids, we present here a full characterization study. The dual nature of these particles, combining intrinsic vesicle features with polymer colloid properties, requires characterization methods that address both the morphology (cryo-TEM, AFM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 31 publications
3
56
3
Order By: Relevance
“…Additionally, we were able to demonstrate that the phase separation phenomenon in this particular system (DODAB vesicles and polystyrene) is largely independent of process parameters like the molecular weight of the polymer, the initiating chemistry and the polymerization temperature. [11] It could, however, be argued that the expected morphology of polymerization reactions in vesicles would depend on the mutual miscibility of monomer/polymer and surfactant matrix. [3] To investigate the relationship between the chosen surfactant/polymer combination, the applied reaction conditions and the final vesicle±polymer morphology, we performed the present study using a wide variety of polymers and surfactants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we were able to demonstrate that the phase separation phenomenon in this particular system (DODAB vesicles and polystyrene) is largely independent of process parameters like the molecular weight of the polymer, the initiating chemistry and the polymerization temperature. [11] It could, however, be argued that the expected morphology of polymerization reactions in vesicles would depend on the mutual miscibility of monomer/polymer and surfactant matrix. [3] To investigate the relationship between the chosen surfactant/polymer combination, the applied reaction conditions and the final vesicle±polymer morphology, we performed the present study using a wide variety of polymers and surfactants.…”
mentioning
confidence: 99%
“…A similar, albeit less pronounced, behavior has been found for the photopolymerization of styrene in DODAB vesicles at 60 C, i.e., above the phase transition of DODAB vesicles. [11] It is important to note that the DMPC bilayer is visualized here in the so-called rippled phase, [17] P b ¢, just below the main phase transition temperature which gives rise to the faceted contours.…”
mentioning
confidence: 99%
“…[6] In attempts to polymerize monomer that is confined within the hydrophobic interior of a vesicle bilayer, van Herk and co-workers found that strongly localized polymerization could occur to form small polymer beads entrapped in the bilayer. [7] The reason for this unexpected behavior was that local initiation of monomer in the bilayer would locally deplete monomer and create a driving force for diffusion towards the site of propagation. This then leads to the growth of a polymer bead at the expense of monomer elsewhere in the vesicle bilayer.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Jung et al have contested this aspect, and in their studies have clearly demonstrated the phase separation of the polymer particle within the vesicular bilayer, forming what they term as ''parachute-like vesicles'' [89]. It is evident that the miscibility of the monomer in the hydrophobic bilayer region does not guarantee the miscibility of the polymer formed and therefore, more often than not one expects that, as the polymerization proceeds, collapse of the polymer chain will occur, leading to nucleation and precipitation of the polymer.…”
Section: Nanostructured Polymersmentioning
confidence: 99%